METHOD OF TEACHING ENGLISH AT ASSALAAM JUNIOR HIGH SCHOOL: A MICRO ETNOGRAPHIC STUDY - FANANI, SYARIF (2011)
The objectives of this paper are to describe (1) the English teaching-learning process activities at Assalaam Junior High School, (2) the methods usually applied by the teacher in English teaching-learning process, (3) the objectives of English teaching-learning process by using some methods, (4) learner's roles and teacher's roles, (5) and strengths and weakness in the implementation of the methods. It is an ethnographic research. The data for this research are the information about teacher and student's attitude in the classroom activities during English teaching-leaning process of the first year of Assalaam Junior High. The object of this research is the methods implemented by the teacher in English teaching-learning process. The data are analyzed by an ethnographic approach by describing in some aspects. The study shows that there are three methods implemented by teacher in English teaching-learning process of Assalaam Junior High School. The methods namely Direct Method (DM), Audio Lingual Method (ALM), and Total Physical Response (TPR). In Direct Method (DM), the objective is to build up oral communication skills between the students by reading and practicing conversation dialog between teacher and students. In Audio Lingual Method (ALM) the objective is to create communicative competence by giving extensive repetition and drilling to the students. And in Total Physical Response (TPR) the objective is to create teaching-learning becomes more enjoyable, fun and less stressful by using right-brain motor skills in combining with various physical responses.